Implementasi Nilai-nilai Pancasila dalam Kebijakan Ekonomi Nasional oleh Kemenko Perekonomian: Implementation of Pancasila Values in National Economic Policy by the Coordinating Ministry for the Economy - Sabrina Royani Azhari; Devina Azzahra Islamiyah; Niarti Setyaningsih; Lintang Ikhlas Akmal Al-Khosyi (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Pancasila, as the foundation of the state and the ideology of the Indonesian nation, plays an important role in guiding development policies, including in the economic sector. This study aims to analyze the implementation of Pancasila's values in national economic policies formulated by the Coordinating Ministry for Economic Affairs. The research method used is qualitative with a descriptive-analytical approach through literature studies, analysis of official government documents, and reviews of strategic policies such as the Medium-Term National Development Plan (RPJMN), Special Economic Zones (KEK), and economic equality programs. The results show that the values of social justice, unity, and the principle of kinship are reflected in policies that ensure equitable access to resources, empower MSMEs, and develop new economic growth centers in the regions. However, challenges such as regional inequality, the dominance of global investment interests, and limited implementation at the regional level remain obstacles. The conclusion of this study emphasizes that although the implementation of Pancasila values in national economic policies has been ongoing, there is a need for strengthened regulations, public participation, and government consistency to ensure the equitable distribution of development benefits. This research contributes to providing an academic perspective on the relevance of Pancasila as a normative guide for national economic policies.